Analisis Pendapatan dan Pengaruh Penggunaan Input Produksi Pada Usahatani Kedelai di Kabupaten Lombok Tengah - Septiadi, Dudi; Suparyana, Pande Komang; Utama FR, Aeko Fria (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
Soybean is a national strategic food crop commodity with high economic potential. Soybean has many products that are desirable to various classes of society. The development of soybean commodity farming is able to drive the economy in the region. This research intends to investigate the costs and income of soybean farming in Central Lombok District and investigate the elements that affect the production of soybean farming in the Central Lombok District. The data gained in this research are primary data with 30 respondents as farmers. Data were analyzed with the Cobb-Douglas production function transformed into the regression function. The results revealed that the average total cost spent by farmers was Rp. 3.694.927/Ha and an average total receipt of Rp. 7.008.000/Ha, so that the average total income earned by farmers is Rp. 3.313.073/Ha. Based on the analysis of influence (statistical T-Test), the variable land area, urea fertilizer, and liquid pesticide have had an influence on soybean farm production. Based on F-Test Statistics, together all the independent variables have had an influence on the production of soybean farming in Central Lombok.